The impact of autoimmune thyroid disease on cognitive and psychiatric disorders: focus on clinical, pre-clinical and molecular studies - Agnieszka Piekiełko-Witkowska; Monika K Duda; Joanna Bogusławska; Urszula Mackiewicz (European Thyroid Journal)
Autoimmune thyroid disease (AITD) is the most prevalent organ-specific autoimmune condition, encompassing Graves’ disease (typically linked with hyperthyroidism) and Hashimoto’s thyroiditis (generally associated with hypothyroidism). The growing body of evidence suggests that AITD can interfere with brain function. Here, we review the impact of AITD on cognition, mood, and psychiatric disorders by analysing data from clinical, animal, ex vivo and in vitro studies to reveal the molecular mechanisms by which AITD affects brain function. Most reports indicate a stronger association between cognitive impairments and hyperthyroidism (including AITD-related) than hypothyroidism. Both hypothyroidism and hyperthyroidism are linked with a higher risk of depression. At least some of those effects can be mediated by altered concentrations of T3 (3,3′,5-triiodo-L-thyronine), which regulates gene expression in the brain microenvironment, affecting neurogenesis, angiogenesis, neurotransmitter release, and synaptic transmission. Diminished TSH (thyrotropin) signalling may also impair learning and memory by inhibiting the Wnt5a-β-catenin pathway. Thyroid disorders may also contribute to neurodegeneration by T3-mediated attenuation of amyloid-β elimination or TRH-induced formation of neurofibrillary tangles. Surprisingly, most clinical studies do not specify the immune origin of hypothyroidism or hyperthyroidism, therefore further studies involving large, well-characterised patient cohorts are needed to clarify the relationships between AITD and cognitive impairments and psychiatric disorders. Furthermore, data on the effect of anti-thyroid antibodies on brain function are scarce and inconclusive. Given the association between hyperthyroidism and an increased risk of dementia, cognitive impairment and mood disorders, adequate treatment and careful monitoring of AITD patients are essential to prevent the induction of exogenous hyperthyroidism.